Review of Child Punishment In The Juvenile Criminal Justice System (A Coparative Study Between Indonesia And The United States) - Jesslyn Nathania (Dinasti Research, 2024)
Comparative law is one of the methods for learning the law. For legal researchers, aside from looking from the historic perspective, it is also useful to compare the laws between respective countries, be it a whole legal system as in between legal traditions of civil law and common law or comparing between a micro system such as juvenile justice systems in each country for some purposes. Researchers could benefit from using comparative law to look for similarities or differences between legal systems or in the future they could use it for solution in the domestic law to be even better. In this paper, we will compare youth justice system between Indonesia and United States, specifically California State. Youth justice system in Indonesia has this unique sub-system called diversion and restorative justice. The main purpose of it is so children who conflicted with the law have chances to redeem themselves and build reconciliation with the victims and their families. There are also different rights set for the children written in the Code such as the hearing process must be enclosed, and their identity must not be exposed by the media to public eyes. In the United States, there aren’t so many differences by the book except the bargaining, but they have a special procedure before the initial hearing that is the court will consider if the child’s crime is still fit within the juvenile court jurisdiction or sending them to the criminal court which called by judicial waiver. This means that the child is stripped of their special rights and will go to adult prison if the juvenile court decided they could not handle the case for its nature of crime. When the child is proven to be guilty, they also will be sent to adult prison. Finding similarities and differences between legal systems could be useful for research but doesn’t mean that the legal system is flawed or too good. It needs to be reminded that not all the system or sub-system could be applied to other countries since there are also differences in cultures and practices especially between Western and Asian society.